IMPROVING STUDENTS’ SPEAKING ABILITY USING VIDEO BLOGGING PROJECT - Nur Ismiyati; Hartono Hartono (Jurnal Pendidikan Sultan Agung, 2021)
The objective of this study is to find out the effectiveness video blogging project to improve student speaking ability and how it motivate the student to apply it in their English. The research was guided by a conceptual framework to the using video blogging to improve their motivation to speak English during the process of classroom interaction. The research type was an Classroom Action Research. The subject consisted of 27 students of the eleventh grades of SMA Islam Sultan Agung 1 Semarang in the academic year 2020/2021. The research data were collected using triangulation data (planning, action, reflect and observe), observation for collecting data on student motivation in improving speaking by using video blogging project. Data on speaking ability were analyze using the explanation text, to know the improvement in mean student after first cycle and second cycle. Based on, the students average was 61,7, then second treatment, the students average increase to be 71,7, and the third treatment, the students average was 76. It can conclude that video blogging project can improve student’s speaking ability.